2020
DOI: 10.1177/0954411920946636
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modelling of hybrid stabilization systems for the human lumbar spine

Abstract: Intersomatic fusion is a very popular treatment for spinal diseases associated with intervertebral disc degeneration. The effects of three different hybrid stabilization systems on both range of motion and intradiscal pressure were investigated, as there is no consensus in the literature about the efficiency of these systems. Finite element simulations were designed to predict the variations of range of motion and intradiscal pressure from intact to implanted situations. After hybrid stabilization system impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 63 publications
(103 reference statements)
2
14
0
Order By: Relevance
“…Fusion fixation reduces thoracolumbar motion, as shown in previous studies [ 15 , 19 ]. Lu and Lu found that the short-segment fusion fixed model decreased by 52–94% compared with the intact model [ 20 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Fusion fixation reduces thoracolumbar motion, as shown in previous studies [ 15 , 19 ]. Lu and Lu found that the short-segment fusion fixed model decreased by 52–94% compared with the intact model [ 20 ].…”
Section: Discussionsupporting
confidence: 74%
“…Finite element analysis reconstructs the shape of the spine using computer simulation. It then directly interprets spinal biomechanics changes caused by internal fixation by loading its material parameters and loading conditions and guiding the surgical plan [ 15 ]. Finite element analysis can be repeatedly applied, saving medical resources while safely and efficiently simulating complicated surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion xation reduces thoracolumbar motion, as shown in previous studies [15,19]. Lu and Lu found that the short-segment fusion xed model decreased by 52-94% compared with the intact model [20].…”
Section: Discussionsupporting
confidence: 60%
“…Finite element analysis reconstructs the shape of the spine using computer simulation, and then directly interprets changes of spinal biomechanics caused by internal xation by loading its material parameters and loading conditions, and then guiding the clinical surgical plan [15]. Finite element analysis can be repeatedly applied, saving medical resources, while safely and e ciently simulating some di cult surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, FE modelling has already led to relevant conclusions and supported many preclinical studies, namely in what concerns to IVD behaviour or implant development [8,[37][38][39][40]. Additionally, it has also motivated the development of new computational tools (imaging reconstruction methods, FE solvers or even kinematics simulators) that have later led to wider achievements in biomechanics and tissue engineering [41][42][43][44][45][46][47].…”
Section: Computational Biomechanicsmentioning
confidence: 99%